Experience of using the interactive form of masters’ midterm assessment in a foreign language - Olga V. Igumnova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
A foreign language in a masters degree course is a tool for conducting research and development in certain problem areas determined by the educational program. The reasoning ability and the ability to report the main facts of the work done in a foreign language reflect the students communicative competence. The success of foreign language communication on professionally-oriented topics should be estimated by means of objective descriptors and in a form that allows the examinee to show his readiness for foreign language communication. The purpose of this paper is to identify the optimal forms of master students midterm assessment on Foreign Language in the sphere of Law. The author suggests discussing the practicability of using three forms of the exam: traditional and innovative with the use of two options for organizing interactive work of students in the masters program at the exam in the form of a presentation and discussion of advanced research directions related to criminology, criminal and penal law. The discussion can be conducted collectively or individually in the student teacher mode. The paper presents the evaluation system for masters midterm assessment, evaluation technique and the experience of conducting an exam using all three mentioned above organizational forms of work. The advantages and disadvantages of each midterm assessment form are outlined. Statistical methods (Mann-Whitney U-criterion) for evaluating the effectiveness of the exam indicate that it is advisable to use an interactive form such as an individual presentation of a scientific problem. At the same time, the qualitative characteristics of the results show that the collective discussion of scientific presentations makes it possible to check all the subcompetencies of the students communicative competence in the best and objective way, while the traditional form and the exam in the model of the individual presentation of a scientific problem allow assessing the examinees competence on its separate components partially. Thus, this paper makes the issues of the selection of measurable indicators for the foreign language competence of students actual and allows to intensify the discussion about the methodological component of the procedure for assessing master students ability to communicate.